2017
DOI: 10.1021/acs.jctc.7b01078
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding Interactions: Revised Benchmarks and a New Assessment of Exchange vs Dispersion

Abstract: We present a new analysis of exchange and dispersion effects for calculating halogen-bonding interactions in a wide variety of complex dimers (69 total) within the XB18 and XB51 benchmark sets. Contrary to previous work on these systems, we find that dispersion plays a more significant role than exact exchange in accurately calculating halogen-bonding interaction energies, which are further confirmed by extensive SAPT analyses. In particular, we find that even if the amount of exact exchange is nonempirically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 58 publications
4
63
0
Order By: Relevance
“…A large dispersion contribution is attributable to the close proximity of two large, polarizable, halogen atoms in the interacting molecules, in which case polarization plays a marginal role. As in these studies,, and in others, Syzgantseva and coworkers have classified the net interaction responsible for the halogen bonding interaction they examined as primary and secondary, and have demonstrated that the primary interactions alone cannot describe the total interaction energy between fragments because the secondary interaction were dominant. Moreover, it was argued that whilst the energy due to electrostatics was dominant, the sole importance of the quantum exchange part of the intermolecular interaction can never be overlooked since it constitutes a key role in determining the equilibrium geometry of the entire chemical system.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A large dispersion contribution is attributable to the close proximity of two large, polarizable, halogen atoms in the interacting molecules, in which case polarization plays a marginal role. As in these studies,, and in others, Syzgantseva and coworkers have classified the net interaction responsible for the halogen bonding interaction they examined as primary and secondary, and have demonstrated that the primary interactions alone cannot describe the total interaction energy between fragments because the secondary interaction were dominant. Moreover, it was argued that whilst the energy due to electrostatics was dominant, the sole importance of the quantum exchange part of the intermolecular interaction can never be overlooked since it constitutes a key role in determining the equilibrium geometry of the entire chemical system.…”
Section: Resultsmentioning
confidence: 92%
“…In addition to the studies mentioned above, the importance of dispersion in halogen bonding has been recently discussed on a number of occasions ,. In particular, Anderson et al . have concluded from a study that even if the amount of exact exchange is nonempirically tuned to satisfy known DFT constraints, they observed an overall improvement in predicting dissociation energies when dispersion corrections are applied, a finding which is in contrast to a previous study by Kozuch et al .…”
Section: Resultsmentioning
confidence: 99%
“…allows a contribution of HF exchange over the entire range by a factor of a , while the parameter b allows us to incorporate long‐range asymptotic HF exchange by a factor of ( a + b ). Previously, we and others have shown that maintaining a full 100% contribution of asymptotic HF exchange (i.e., constraining a + b = 1), was essential for accurately describing valence excitations in relatively simple molecular systems. Therefore, in the present work on the streptocyanine system, we fix the parameters a = 0.0 (no short‐range exchange) and b = 1.0 in conjunction with self‐consistently tuning the range‐separation parameter ω in the LC‐ ω PBE functional to satisfy DFT‐Koopmans’ theorem .…”
Section: Theory and Methodologymentioning
confidence: 99%
“…Many correlations were established between the maximum value of the molecular electrostatic potential, V s,max , calculated at the σ-hole and the stabilisation energies of the corresponding XBs. [28][29][30][31][32][33][34][35][36][37] The controversy remains strong, as can be noted from the recent literature on the emblematic case of the Y 3 CÀ I halogenbond donor. [19,27] Some authors opposed other contributions, including dispersion, charge transfer (leading to partial covalent bond formation), and the repulsive component resulting from the Pauli exclusion principle.…”
Section: Introductionmentioning
confidence: 99%
“…[19,27] Some authors opposed other contributions, including dispersion, charge transfer (leading to partial covalent bond formation), and the repulsive component resulting from the Pauli exclusion principle. [28][29][30][31][32][33][34][35][36][37] The controversy remains strong, as can be noted from the recent literature on the emblematic case of the Y 3 CÀ I halogenbond donor. [38][39][40][41] While studying the XB interactions between Y 3 CÀ I (Y=F to I) and the Cl À and NMe 3 Lewis bases, Huber and co-workers highlighted unexpected trends regarding the interaction strengths.…”
Section: Introductionmentioning
confidence: 99%